1999
DOI: 10.1001/jama.281.13.1182
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cardiopulmonary Resuscitation Prior to Defibrillation in Patients With Out-of-Hospital Ventricular Fibrillation

Abstract: HERE IS LITTLE DOUBT THAT SPEED in providing care represents the major determinant of survival for patients with out-ofhospital ventricular fibrillation (VF). That relationship has been documented for initiation of cardiopulmonary resuscitation (CPR) 1,2 as well as for the arrival of personnel and devices necessary for defibrillation. 3,4 Since 1970, the pattern for delivering out-of-hospital emergency care in Seattle, Wash, has incorporated rapidly responding first units staffed by emergency medical technicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
247
3
22

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 649 publications
(288 citation statements)
references
References 20 publications
16
247
3
22
Order By: Relevance
“…It is controversial whether OHCA victims should be treated with CPR before defibrillation when the AED pads are attached to the OHCA patients [27][28][29][30]. It is generally recommended that single bystander should going for AED after witnessing patient collapse only when they can see an AED at the scene [9].…”
Section: Discussionmentioning
confidence: 99%
“…It is controversial whether OHCA victims should be treated with CPR before defibrillation when the AED pads are attached to the OHCA patients [27][28][29][30]. It is generally recommended that single bystander should going for AED after witnessing patient collapse only when they can see an AED at the scene [9].…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular fibrillation (VF) is the first recorded electrocardiographic rhythm in approximately 30% of sudden cardiac death events in the out-of-hospital setting [1,2]. Three large studies of cardiac arrest have demonstrated that when cardiopulmonary resuscitation (CPR) is performed for one and one half to three minutes prior to defibrillation there is an associated increase in survival of over 10% percent [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Three large studies of cardiac arrest have demonstrated that when cardiopulmonary resuscitation (CPR) is performed for one and one half to three minutes prior to defibrillation there is an associated increase in survival of over 10% percent [1][2][3]. The increased survival is due almost exclusively to greater survival (approximately 15%) in the group of patients with VF duration of over 4 to 5 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the guideline was also applied to manual defibrillation, with no discernable rationale. 3 The poor results from deferred defibrillation in hospitals may be largely due to the fact that the great majority of defibrillations in that setting are manual. Deferring defibrillation to mitigate hands-off time is completely inappropriate with manual defibrillation; with a manual device, a shock can be delivered in less than 5 seconds if done correctly.…”
mentioning
confidence: 99%
“…The same guidelines also recommended 2 minutes of cardiopulmonary resuscitation (CPR) prior to the initial and each subsequent defibrillation attempt, providing substrate to the myocardium and increasing the likelihood of shock success. [2][3][4] The underlying physiological concept is described by Weisfeldt and Becker as part of their 3-phase model of ventricular fibrillation. 2,5 Large randomized out-of-hospital studies have demonstrated that high-quality CPR may "prime" the heart before defibrillation, as suggested by the 3-phase model.…”
mentioning
confidence: 99%